Electrified hydraulic power steering system in hybrid electric heavy trucks. Issue 3 (1st September 2014) - Morton, Christopher; Spargo, Christopher M.; Pickert, Volker
Abstract : Over the last 20 years, conventional automotive engine ancillaries have migrated from being mechanically powered to electrically powered in order to meet market demand. To adopt this trend in heavy trucks requires a higher power electrical system in order to cope with the higher loads placed upon it. Until the advent of the hybrid electric heavy truck (HET) this power infrastructure has not been available. HET's require a higher voltage system in order to reduce losses and provide adequate power and voltage levels for the traction motor. This study investigates for the first time the benefit of electrifying a hydraulic power assisted steering system in an HET. The developed electrical hydraulic power steering (EHPS), using a high‐voltage traction battery, is found to drastically reduce the consumed energy over a drive cycle by optimal operation of the pump over the driving cycle. Empirical data from a prototype HET with EHPS confirms the simulation results from Dymola.